A study on the impact of official promotion short videos on tourists’ destination decision-making in the post-epidemic era - Jiang, Jing; Hong, Yuxin; Li, Wenwen; Li, Ding (Frontiers in Psychology, 2022)
The COVID-19 pandemic has had an enormous impact on traditional tourism. Influenced by the uncertainties of the current epidemic, to revive the development of tourism and local economics, local governments have used short video accounts to release tourist promotion short videos for publicizing and marketing. This study takes official promotion short videos as the research object, establishes a structural equation model based on the SOR theory, and explores the influencing factors of official short videos on tourists’ destination decisions through empirical analysis. It finds that the official promotion short videos can positively stimulate users’ perception and sentiments significantly due to the three unique features of authority, interactivity and interest, thus influencing tourists’ destination decision-making behavior. On this basis, this study proposes to improve the operation of an official short video from three aspects: enhancing the authority of official short video accounts, attaching importance to the interactive mechanism, and strengthening the creativity of short videos. It is hoped that the study may help enhance the influence of official promotion short videos and promote the high-quality development of local tourism.